THE MODEL OF CONSOCIATIONAL DEMOCRACY, PRESENTED THROUGH THE EXAMPLE OF THE SWISS CONFEDERATION - Bochvarska, Daniela (International Scientific Journal Vision, 2025)
In this paper, it is spoken about the model of consociational democracy and its practical application in plural societies which are heterogeneous, which have gone through internal conflicts and which often are characterized by a certain line of division of the citizens on ethnic, religious, or linguistic basis. Often, this model represents the only possible solution for deeply divided societies, providing a stable political system, as opposed to deep societal segmentation. The model of consociational democracy was designed with the aim to correct certain shortcomings of the majoritarian model which referred primarily to the right of the majority to introduce policies and to elect representatives. The majoritarian model of democracy, based on the will of the majority and the principle “winner takes all,” excludes the will of minorities and disables them from having their own input in decision-making, as well as their own political representatives. The consociational model of democracy, on the other hand, includes the will of more individuals, enabling greater democratization in the countries where it is applied. There were doubts that the emergence of the consociational democracy model would not be suitable for small European democracies, emphasizing the differences between this model of democracy in some smaller European states and the majoritarian model that dominated in the United Kingdom, the USA, and France. However, the example of Switzerland shows the opposite. By applying the method of content analysis and using official data from relevant institutions, this paper analyzes the model of consociational democracy in Switzerland. This model is typical for this federal state, which continuously strengthens opportunities for democratic participation. The use of various instruments that include minorities as much as possible, along with decision-making based on consensus and negotiations among parties, represents a vital political characteristic of this small European state with a wide range of diversity.